2018
DOI: 10.1016/j.polymer.2018.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Strictly linear polyethylene using Co-catalysts chelated by fused bis(arylimino)pyridines: Probing ortho-cycloalkyl ring-size effects on molecular weight

Abstract: Six examples of α,α'-bis(arylimino)-2,3:5,6-bis(pentamethylene)pyridine-cobalt(II) chlorides, [2,3:5,6-{C4H8C(NAr)}2C5HN]CoCl2 (Ar = 2-(C5H9)-6-MeC6H3 Co1, 2-(C6H11)-6-MeC6H3 Co2, 2-(C8H15)-6-MeC6H3 Co3, 2-(C5H9)-4,6-Me2C6H2 Co4, 2-(C6H11)-4,6-Me2C6H2 Co5, 2-(C8H15)-4,6-Me2C6H2 Co6), containing N-aryl groups that differ in either the ring size of the ortho-cycloalkyl substituents or the para-R group (R = H, Me), have been synthesized using a one-pot template approach. The molecular structure of Co1 highlights … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 47 publications
(87 citation statements)
references
References 44 publications
(72 reference statements)
7
80
0
Order By: Relevance
“…By varying the test temperature from 10 to 60°C (runs 4 and 6-10, 3 Research 1:82 × 10 6 gðPEÞ mol -1 ðFeÞ h -1 was observed at 20°C. It was also evident that the molecular weight of the polyethylene gradually decreased from 9.5 to 1.2 kg mol -1 as the temperature was raised which can be credited to increased chain transfer at higher temperature [4,22,26,27,[32][33][34][35][36][37][38]. Meanwhile, the molecular weight distribution narrowed as the temperature was raised (M w /M n : from 13.2 to 2.2), an observation also noted at higher ethylene pressure (vide infra) and elsewhere [4,32,36].…”
Section: Catalytic Evaluation Of Fe1-fe5mentioning
confidence: 76%
See 2 more Smart Citations
“…By varying the test temperature from 10 to 60°C (runs 4 and 6-10, 3 Research 1:82 × 10 6 gðPEÞ mol -1 ðFeÞ h -1 was observed at 20°C. It was also evident that the molecular weight of the polyethylene gradually decreased from 9.5 to 1.2 kg mol -1 as the temperature was raised which can be credited to increased chain transfer at higher temperature [4,22,26,27,[32][33][34][35][36][37][38]. Meanwhile, the molecular weight distribution narrowed as the temperature was raised (M w /M n : from 13.2 to 2.2), an observation also noted at higher ethylene pressure (vide infra) and elsewhere [4,32,36].…”
Section: Catalytic Evaluation Of Fe1-fe5mentioning
confidence: 76%
“…As an alternative strategy in bis(imino)pyridine ligand design, our group has recently explored the fusion of carbocycles to the central pyridine unit in (Figure 1) as a means to form well-defined Fe-/Co-based complexes bearing singly [22][23][24][25][26][27][28][29][30] and doubly fused derivatives (e.g., B, C, D, and E in Figure 1) [31][32][33][34][35][36][37][38]. Indeed, the fused ring size has been shown to be pivotal to the catalytic activity and polymeric properties [6,[36][37][38].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cr5, R 1 = F, R 2 = CHPh2 Cr6), in moderate to good yield (30 -81%) (Scheme 1). The free ligands were not amenable to isolation and so the above template approach was undertaken to afford the complexes in one step; similar one pot approaches have been employed elsewhere [51,[61][62][63][64][65][66][67]. All the chromium(III) complexes were air stable green solids that have been characterized by infra-red spectroscopy and by microanalysis.…”
Section: Resultsmentioning
confidence: 99%
“…Above 20 o C, the activity steadily decreased reaching its lowest value of 0.75 × 10 5 g(PE) mol -1 (Cr) h -1 at 60 o C (entry 5, Table 4) which can be accredited to the onset of catalyst deactivation [48,62,[65][66][67]. In terms of molecular weight, the corresponding polymers followed a similar downward trend (Mw: from 106.6 to 21.9 kg mol -1 ) on increasing temperature which can be ascribed to chain transfer occurring faster than chain propagation under these conditions [43,50,[68][69].…”
Section: <Table 3>mentioning
confidence: 99%